The Comparison of Self-esteem and Premarital Sexual Behavior in Teenagers between Ex-localization Areas and Surrounding Areas in Surabaya - Retno Indarwati; Clauvega Myrtha Sunarya; Elida Ulfiana (Universitas Airlangga, 2020)
Introduction:Adolescence is a vulnerable period involving behavior irregularities, especially premarital sexual behavior. Premarital sexual behavior can be caused by personal and social factors. This study aimed to analyze self-esteem and premarital sexual behavior in teenagers between Dolly ex-localization and the surrounding area in Surabaya. Methods: This study used a quantitative approach with a descriptive comparative method. The population was teenagers who were not married. The sample was 118 teenagers, consisting of 59 teenagers in ex-localization and 59 teenagers in the surrounding area. The variables were self-esteem and premarital sexual behavior in teenagers who live between ex-localization and the surrounding area. Data were collected with a questionnaire and analyzed using Mann-Whitney U Test with a level of significance α=0,05. Results: Results showed that there was no difference in self-esteem level between teenagers in ex-localization and the  surrounding area (p = 0.568); there was a difference in premarital sexual behavior between teenagers in ex-localization and the surrounding area (p = 0.017). It can be concluded that both teenagers between ex-localization and surrounding area had high levels of self-esteem and were in a high risk category for premarital sexual behavior. Teenagers in ex-localization areas have better levels of self-esteem than teenagers in the surrounding area but have a high risk in premarital sexual behavior. Conclusion: Further studies should include more variables such as the relationship between parents and their children, peer group, and social group. T